Treatment Response of PlatinumBased Chemoradiation on Locally Advanced Cervical Cancer - Khonsa, Oni; Purbadi, Sigit; Supriana, Nana; Sutrisna, Bambang (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To evaluate the efficacy (treatment response), toxicity, and overall survival of concomitant chemoradiation (CRT) with three-weekly cisplatin-ifosfamide compared to CRT with weekly cisplatin in advanced stage cervical cancers (stage IIB-IIIB). Method: This is a historical cohort between 32 patients receiving CRT with three-weekly cisplatin and ifosfamide and 29 patients receiving weekly cisplatin in Gynecologic Oncology division outpatient clinic and ward, Dr. Cipto Mangunkusumo Hospital. Results: There was no significant difference in treatment response, overall and disease-free survival. There was more gastrointestinal toxicity in the cisplatin-ifosfamide arm compared to the other arm (p=0.014), but other toxicity effects were not different. Conclusion: Platinum based-chemoradiation has the same efficacy in terms of treatment response for locally advanced cervical cancer. [Indones J Obstet Gynecol 2015; 3-4: 212-221] Keywords: cisplatin, concomitant chemoradiation, ifosfamide, locally advance stage cervical cancer